The memory and memorialization of James Birdseye McPherson - Dudley, Eric A. (Kansas State University, 2016)
General James Birdseye McPherson, the highest ranking Union officer killed during the Civil War, slowly over time became a largely forgotten figure in the collective memory of most Americans. A brief examination of the general's personal life and military career reveals that his life's narrative presented a captivating story, one which successfully captured the attention of his contemporaries. In the fifty years following his death, several groups of interested individuals sought to honor the general's memory through the construction of memorials. This dissertation approaches the history of McPherson through a memory study focusing particularly on the general's memorialization and the four main locations where the general had monuments built in his honor. In Washington, D.C., Clyde, Ohio, Atlanta, Georgia, and McPherson, Kansas, the attempts to preserve McPherson's memory both succeeded in certain ways but also fell short of accomplishing their primary goal. In the process of memorialization the general was both remembered and forgotten. The funding, unveiling, and preserving of the various monuments illuminates the politics of commemoration as well as the motives behind those seeking to honor McPherson. With the passing of time, McPherson's memory slowly began to evolve in each location and generally changed to reflect the times and circumstances of the citizens. In each case, the McPherson memorials signified something different to the community, including a permanent reflection of local identity, a symbol of sectional reconciliation, or a means of promoting civic pride and local boosterism. Ultimately, although the memorialization of McPherson served as the best attempt to honor the generals' memory, the narrow scope and reach of memorials could not successfully preserve McPherson's memory beyond a very limited range and within small communities of interested parties.
Keywords: McPherson; Memorialization; James Birdseye McPherson; Monument; Memorial; Memory